PENGARUH TRADISI ARAB PRA ISLAM TERHADAP HUKUMAN RAJAM - Ali Ali (Universitas Islam Negeri Ar-Raniry, 2014)
This article was written to answer the question of how the punishment of adultery in the tradition of pre-Islamic Arabia and whether the punishment of stoning in adultery punishment traditions influenced by pre-Islamic? This is also done as most of the literature (especially fiqh) which is likely to assume muhsan stoning sentence for the perpetrator is Sunnah and is therefore considered final. This is different from the Qur'an which contains only the caning without perpetrator category. The author uses socio-historical approach to look at the possibility of the adoption of pre-Islamic law in jurisprudence historically recognized authority but had methodological problems. Of search performed, there were no rules on punishment of adultery in the religion of Jahiliah. The punishment for adultery, which are so cruel, is found in the ancient Egyptian Penal Code, the laws of Hammurabi, and the Old Testament. Original stoning is not Islam. This punishment has been published in the books before the Islam religion. Islam then adopted with improvements in many facets.